Formation of Project Culture in Future Teachers - Haleta, Yaroslav; Kozlenko, Volodymyr; Riabovol, Liliia; Filonenko, Oksana; Kravtsova, Tetiana (Journal of the University of Zulia, 2023)
The purpose of the article is to present the methodology of forming the project culture of future teachers. The methodological basis of the research is: modern ideas of the dialectic of the general, special and individual in the formation of project culture; philosophy of a subjective-humanistic approach to education; theoretical provisions about the social, active and creative essence of the individual, the mechanisms and conditions of its self-expression in culture; the theory of complex personality development and the formation of knowledge, abilities and skills; fundamental studies of the development of the general and professional culture of the teacher. Today, students have to cope with a large volume of tasks, have time to live and study. At the same time, today most students are not ready for the challenges of modern society. The process of forming a project culture should be aimed at creating a project-innovative environment in an educational institution, that is, creating conditions for the emergence, development and implementation of projects. Project-based learning targets future teachers for academic, personal, and career success, and prepares them for the challenges they will face in their future careers.